Disseminability of computerized cognitive training: Performance across coaches. Issue 2 (3rd April 2019) - Fournier-Goodnight, Ashley S.; Ashford, Jason M.; Clark, Kellie N.; Martin-Elbahesh, Karen; Hardy, Kristina K.; Merchant, Thomas E.; Jeha, Sima; Ogg, Robert J.; Zhang, Hui; Wang, Lei; Conklin, Heather M.
ABSTRACT: Cogmed is a computerized cognitive intervention utilizing coaches who receive standardized instruction in analyzing training indices and tailoring feedback to remotely monitor participant's performance. The goal of this study was to examine adherence, satisfaction, and efficacy of Cogmed across coaches. Survivors of pediatric brain tumors and acute lymphoblastic leukemia ( N  = 68) were randomized to intervention (Cogmed) or waitlist control. The intervention group was matched with one of two coaches. Cognitive assessments were completed before and after intervention, and participants and caregivers in the intervention group completed satisfaction surveys. T-tests showed no differences in adherence across coaches (number of sessions completed p  = .38; d  = .32). Noninferiority statistics were not consistently equivalent for satisfaction, but equivalence was supported for caregiver perceptions of pragmatic utility and participant perceptions of logistical ease of Cogmed. Equivalence was not consistently suggested for cognitive outcomes, but was supported on measures tapping relevant cognitive domains (attention, working memory, processing speed, academic fluency). This study suggests adherence can be maintained across coaches. While aspects of satisfaction and cognitive outcomes were equivalent, the possible influence of coach-based variables cannot be ruled out. Findings highlight challenges in standardizing the coaching component of multicomponent computerized interventions and the need for ongoing research to establish dessiminability.